2010
DOI: 10.1016/j.ultrasmedbio.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Chlorambucil Using an Acoustically-Triggered Perfluoropentane Emulsion

Abstract: Ultrasound-mediated delivery systems have mainly focused on microbubble contrast agents as carriers of drugs or genetic material. This study utilizes micron-sized, perfluoropentane (PFP) emulsions as carriers for chlorambucil (CHL), a lipophilic chemotherapeutic. The release of CHL is achieved via acoustic droplet vaporization (ADV), whereby the superheated emulsion is converted into gas bubbles using ultrasound. Emulsions were made using an albumin shell and soybean oil as the CHL carrier. The ratio of the PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 45 publications
5
126
0
Order By: Relevance
“…Larger droplets undergo a phase-transition more efficiently [10], but also have a higher probability of occluding pulmonary capillaries. Another limitation is the maximum concentration of droplets within the blood stream that can be tolerated by the body.…”
Section: Computed Droplet Size Distributions and Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger droplets undergo a phase-transition more efficiently [10], but also have a higher probability of occluding pulmonary capillaries. Another limitation is the maximum concentration of droplets within the blood stream that can be tolerated by the body.…”
Section: Computed Droplet Size Distributions and Concentrationsmentioning
confidence: 99%
“…Micron-sized perfluorocarbon microbubbles created via ADV have been shown to occlude capillary beds and arterioles, which can facilitate embolotherapy in cancer treatment [3,7,8]. Previous studies have also demonstrated ADV-mediated delivery of chemotherapeutic drugs such as paclitaxel [9], chlorambucil [10], and doxorubicin [11] loaded in perfluorocarbon droplets. Thermal ablation of cancerous lesions has been enhanced using perfluorocarbon droplets as cavitation nuclei during high intensity focused ultrasound (HIFU) exposure [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Two such applications requiring many millions of droplets include site-specific therapeutics using oil-in-water droplets and next generation sequencing using water-in-oil droplets. In particular, the phase-change droplets in this study, at 9.8 lm in diameter, are amenable to intra-arterial administration 30 as gas embolotherapy (i.e., targeted vessel occlusion) agents for the treatment of various hypervascular cancers, as these droplets are stable at room temperature yet undergo rapid liquid-to-gas phase transition above a uniform acoustic or thermal activation threshold. 23 Using a more precise method to fabricate the channel geometries to be equal, the flow rate ratio could be increased in the dripping regime to stably generate smaller therapeutic droplets suitable for intravenous injection, 23,30 or sub-micron droplets for extravascular applications alongside medical ultrasound.…”
Section: E Applicationsmentioning
confidence: 99%
“…In particular, the phase-change droplets in this study, at 9.8 lm in diameter, are amenable to intra-arterial administration 30 as gas embolotherapy (i.e., targeted vessel occlusion) agents for the treatment of various hypervascular cancers, as these droplets are stable at room temperature yet undergo rapid liquid-to-gas phase transition above a uniform acoustic or thermal activation threshold. 23 Using a more precise method to fabricate the channel geometries to be equal, the flow rate ratio could be increased in the dripping regime to stably generate smaller therapeutic droplets suitable for intravenous injection, 23,30 or sub-micron droplets for extravascular applications alongside medical ultrasound. 31 The module presented here may also serve emerging methods in next generation sequencing, with the potential to dispense single DNA templates and primer (e.g., on a bead) into several hundreds of millions of small droplets within a quarter hour, facilitating the amplification and enrichment of single DNA templates with enhanced throughput and scalability yet reduced reagent consumption.…”
Section: E Applicationsmentioning
confidence: 99%
“…The severe side effects of the systemic injection of chemotherapeutic drugs on healthy tissue can potentially be lowered by encapsulation of the drug in phase-change droplets [187][188][189] . The droplets typically consist of a low boiling point perfluorocarbon oil, such as perfluoropentane (T b = 29 ‱ C), and they do not spontaneously vaporize when injected in-vivo until the droplets are exposed to a high pressure ultrasound pulse 165,171 .…”
Section: Introductionmentioning
confidence: 99%